Development and validation of the Disrespect and Mistreatment during Childbirth Questionnaire: risk factors and effects on parenting stress - Suttora, Chiara; Nardozza, Odette; Menabò, Laura; Preti, Emanuele; Passaquindici, Ilenia; Fasolo, Mirco; Spinelli, Maria (Frontiers in Psychology, 2025)
IntroductionA growing body of research indicates that disrespect and mistreatment during childbirth (obstetric mistreatment) are widespread globally. These experiences, along with their prevalence, risk factors, and impacts on maternal mental health, are often assessed using ad hoc tools, highlighting the need for psychometrically valid instruments. This study aims to develop and validate the Disrespect and Mistreatment during Childbirth Questionnaire (DMCQ) and explore factors contributing to negative childbirth experiences, as well as the relationship between mistreatment and parenting stress during the first two postpartum years.MethodsAn online survey was administered to 620 women, assessing sociodemographic and childbirth-related factors, experiences of disrespect and mistreatment during childbirth, postpartum posttraumatic stress symptoms related to childbirth, personality traits, and parenting stress.ResultsExploratory factor analysis identified a 5-factor model with good internal consistency: negative interactions with healthcare providers, separation from the newborn, medical intrusiveness, verbal mistreatment, and pain experience. Confirmatory factor analysis supported this structure, showing positive correlations with perinatal stress (convergent validity) and no association with openness to experience (divergent validity). Higher scores on the DMCQ correlated with increased parenting stress, particularly distress related to the parental role. Women with higher education, low income, and births in Southern Italy reported greater obstetric mistreatment. Risk factors included primiparity, unplanned cesarean, instrumental delivery, episiotomy, anesthesia, labor exceeding 12 h, and delivery complications.DiscussionIn conclusion, the Disrespect and Mistreatment during Childbirth Questionnaire is a psychometrically valid tool specifically designed to address obstetric mistreatment in the early years postpartum.